Design, Development and in vitro Evaluation of Hydrogels Prepared by Free Radical Polymerization of Acrylic Acid (AAc) Containing a Model Antidiabetic Drug - Talukdar, Apurba; Shivakumar, Satish Chowdahalli (Indian Journal of Pharmaceutical Education and Research, 2023)
Introduction: The controlled release of medicaments in the management of diabetes is desirable to have a better therapeutic activity of the drug. Objectives: In the present study hydrogels were prepared as a controlled drug delivery system taking Rosiglitazone as a model drug. Materials and Methods: Hydrogels were created using the Free Radical Polymerization approach, with the crosslinker N, N′-Methylene bisacrylamide serving as a binding agent for the polymerization. To create a polymeric network, ammonium persulphate has been used as a polymerization inducer for AAc to poly (acrylic acid) in the existence of polyvinyl alcohol (PVP). A maximum of fifteen formulations were created with various concentrations of polymers and crosslinking agents to test the swelling, diffusion coefficients, ESR, and in vitro drug release properties of the drugs tested. The FT-IR and DSC techniques were used to determine the drug's compatibility with the polymers. The XRD studies were carried out to understand the nature of the drug contained within the hydrogel formulation. The morphologies of the surface were determined using SEM. Results and Discussion: A greater swelling was observed in the basic pH range and a marginal swelling was observed in the acidic pH range according to the swelling studies. The ESR affirmed that the pH of the hydrogels was indeed a factor in the swelling of the gels. The results of the diffusion study revealed that the diffusion coefficient has risen as a result of the reduction in cross-linker concentration and the increase in acrylic acid concentration in the solution. The in vitro release of drug data revealed that the swelling has been increased as a result of the increased concentration of acrylic acid, which resulted in the increased release of the drug. However, when the concentrations of PVP and cross-linker were increased, it was discovered that the drug release was decreased. Conclusion: AAc-PVP based hydrogel was found to be a promising controlled drug delivery system for the treatment of Rosiglitazone, according to the findings of this study.
Keywords: Hydrogels; PVP Acrylic acid; Free Radical Polymerization; Antidiabetic Drug